Project-Based Learning in Senior High School Chemistry under Kurikulum Merdeka: A Systematic Review - Zia Ur Rehman; Sri Atun (Universitas Tidar, 2026)
The rapid transformation of 21st-century education requires teaching approaches that promote critical thinking, creativity, collaboration, and problem-solving skills. This systematic review examines the implementation of Project-Based Learning (PjBL) in senior high school chemistry and its alignment with the competency-based objectives of Kurikulum Merdeka. The review followed the PRISMA 2020 guidelines. Studies were included if they reported empirical findings on the use of PjBL in secondary-level chemistry, while non-empirical and non-chemistry studies were excluded. Literature searches were conducted on 17 October 2025 across Scopus, ERIC, DOAJ, Google Scholar, and Garuda databases. A total of 49 studies (50 reports) met the inclusion criteria. Due to variations in research designs and outcome measures, findings were synthesized using a narrative approach. The reviewed studies addressed various chemistry topics, including redox reactions, acid–base concepts, hydrocarbons, colloids, thermochemistry, and green chemistry. Overall, most studies reported positive learning outcomes such as improved conceptual understanding, motivation, critical thinking, and academic achievement. However, methodological limitations were identified, particularly the predominance of research and development (R&D) studies and the limited use of rigorous experimental designs. These findings suggest that PjBL represents a flexible and contextually relevant pedagogical approach for senior high school chemistry within Kurikulum Merdeka.